Results and evaluation of US Navy shock trial environmental mitigation of marine mammals and sea turtles - Clarke , Janet T.; Norman , Stephanie A. (J. Cetacean Res. Manage., 2023)
A shock trial of a US Navy Destroyer, the USS Winston S. Churchill, was conducted offshore of northern Florida in May and June 2001. The shock trial consisted of three underwater detonation tests, spaced approximately one week apart. Environmental mitigation to minimise the impact of the shock trial on marine mammals and sea turtles was based on a Safety Range of 3.7km (2 n.miles) radius around the detonation site, and a Buffer Zone of an additional 1.85km (1 n.mile) radius beyond the Safety Range. Mitigation included site selection surveys, pre-detonation aerial, vessel and bio-acoustic monitoring, and post-detonation aerial and vessel monitoring. Six species of odontocete and two species of sea turtle were identified during mitigation monitoring, as well as several sightings that could not be identified by species. Site selection aerial surveys were implemented to select a test site with the lowest abundance of marine mammals and sea turtles. Nearly 300 animals were seen during site selection surveys. Pre-detonation aerial and vessel monitoring was implemented to sight any marine mammal and sea turtle within the Safety Range on designated test days, and track the animals until they could be verified to be outside the Safety Range. Approximately 1,200 marine mammals and 32 sea turtles were sighted during pre-detonation monitoring. Pre-detonation bio-acoustic monitoring was implemented to detect large cetaceans within the Safety Range and Buffer Zone; the only calls heard were from dolphins that could not be localised. Post-detonation monitoring was implemented to determine the effectiveness of mitigation procedures. No injured or dead marine mammals or turtles were detected during approximately 185 hours of post-detonation aerial and vessel visual monitoring. Post-detonation monitoring resulted in observations of 767 marine mammals and 42 sea turtles. With only two exceptions, the same marine mammal and sea turtle species were observed prior to, during and after the shock trial test time period. Factors leading to the success of this environmental mitigation effort are summarised, and recommendations for improvements to mitigation efforts of this size and scope are suggested. These recommendations include the use of a simultaneous second aircraft for improved coverage during pre-detonation surveys, increased post-detonation aerial monitoring, equitable survey data for all test sites under consideration during planning stages, and reassessment of bio-acoustic monitoring need and purpose.